A case of leukemia cutis showing annular erythema during the course of Philadelphia chromosome‐positive acute B‐lymphoblastic leukemia - Hizuru Tomita; Yoshimasa Nobeyama; You Sakayori; Rika Matsumoto; Satomi Chujo; Hikaru Suzuki; Akihiko Asahina (Clinical Case Reports, 2024)
Key Clinical Message We report a case of leukemia cutis showing annular erythema during the course of Philadelphia chromosome‐positive acute B‐lymphoblastic leukemia. The annular appearance may be developed by immunomodulatory effects of blinatumomab.